PENGARUH PEMBIAYAAN SYARIAH TERHADAP PERTUMBUHAN USAHA KECIL DAN MENENGAH PERSPEKTIF EKONOMI ISLAM - Dahliati Simanjuntak; Rayanti Renawa; Sumintan Alifiyah (Adpertens: Jurnal Ekonomi dan Manajemen, 2025)
This article aims to analyze the effect of Islamic financing on the growth of small and medium enterprises (SMEs) from an Islamic economic perspective. SMEs play an important role in the national economic structure, but access to capital is often a major obstacle. Islamic financing is an inclusive alternative that promotes the principles of justice, profit sharing, and business prosperity. This study uses a quantitative and qualitative approach with field surveys and in-depth interviews with SME actors who receive financing from Islamic financial institutions. The results show that Islamic financing not only contributes to an increase in working capital but also fosters ethical awareness, social responsibility, and business sustainability. Financing based on mudharabah and musyarakah contracts encourages mutually beneficial partnerships and reduces the risk of exploitation. From an Islamic economic perspective, business growth is measured not only quantitatively, but also in terms of usefulness and blessings. Therefore, the influence of Islamic financing on SMEs is multidimensional. This study recommends strengthening the managerial capacity of SME actors and developing an adaptive Islamic financing monitoring system. These findings are relevant for policymakers, academics, and Islamic financial institutions in promoting an inclusive and equitable economy